Iterated local search for the capacitated vehicle routing problem with sequence‐based pallet loading and axle weight constraints. Issue 3 (13th March 2017) - Pollaris, Hanne; Braekers, Kris; Caris, An; Janssens, Gerrit K.; Limbourg, Sabine
Abstract : In this article an Iterated Local Search algorithm for the capacitated vehicle routing problem with sequence‐based pallet loading and axle weight constraints is presented. Axle weight limits impose a great challenge for transportation companies. Yet, the literature on the incorporation of axle weight constraints in vehicle routing models is very scarce. The effect of introducing axle weight constraints in a CVRP on total routing cost is analyzed. Results show that integrating axle weight constraints does not lead to a large cost increase. However, not including axle weight constraints in the planning process may induce major axle weight violations. © 2017 Wiley Periodicals, Inc. NETWORKS, Vol. 69(3), 304–316 2017